The Impact of UP3AI Values on Islamic Religious Education Values and Physics Values in the Qur'an of Physics Education Students - Dewi Kurnia; Elisa Elisa; Nurulwati Nurulwati (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine whether there is an effect of the UP3AI value on the value of Islamic Religious Education and Physics in the Qur'an of physics education students from the 2016 and 2017 batches of the syiah Kuala university. This study uses a quantitative approach. The data used is secondary data with data collection using documentation techniques. The population is all students of physical education class 2016 and 2017 who have completed UP3AI, PAI, and FISQUR courses. At the same time, the sample is as many as 54 samples obtained by the slovin technique from the entire population. Data processing was carried out with multiple regression analyses assisted by the SPPS version 26 application. The results showed an effect of the UP3AI value on the PAI value with a positive regression coefficient of 1.070, stating that for every 1% addition to the UP3AI value, the PAI value increased by 1.070. While the results of the regression of the UP3AI value on the FISQUR value, a negative regression coefficient of -0.331 means that there is no effect of the UP3AI value on the FISQUR value.